2021
DOI: 10.1111/ijn.12980
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual care, compassion and associated factors of midwives working in delivery rooms

Abstract: Aim This study aimed to determine the level of spiritual care and compassion among midwives working in delivery rooms and associated factors. Methods A descriptive design was utilized to collect data using self‐report questionnaires from 181 midwives working in delivery rooms in Turkey. Data were collected between 1 February 2020 and 20 March 2020. Results The mean Spiritual Care‐Giving Scale (SCGS) (min: 25‐ max: 175) and Compassion Scale (CS) (min: 24– max: 120) scores were 147.88 ± 17.84 and 96.37 ± 12.84. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…One of the wellestablished values of spirituality is that it helps people cope with major life stresses (31). Although the present theme was a new nding in the studies, but since midwifery is a profession based on helping others, however, long working hours and their exposure to traumatic birth events affects the level of spiritual care and compassion (32). In a study about the experience of being a mother and a nurse during a pandemic, the participants' religious themes were found to be valuable in coping with the experienced chaos (27).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…One of the wellestablished values of spirituality is that it helps people cope with major life stresses (31). Although the present theme was a new nding in the studies, but since midwifery is a profession based on helping others, however, long working hours and their exposure to traumatic birth events affects the level of spiritual care and compassion (32). In a study about the experience of being a mother and a nurse during a pandemic, the participants' religious themes were found to be valuable in coping with the experienced chaos (27).…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that improving the working conditions of midwives contributes to the quality of maternal health care (32). The doctors who were working in the NHS center required receiving privileges such as rest spaces against mere gratitude (36).…”
Section: Discussionmentioning
confidence: 99%
“…Tis study revealed a concerningly high rate of poor sleep quality among MCH nurses (57.9%), which was higher than that of nurses in the community (46%) [35], psychiatric hospitals (38.1%) [36], and general hospitals (55%) [16]. Tis may be due to diferences in workplaces and workfows between healthcare organisations, as MCH nurses have to deal with challenging situations such as inappropriate children, overbearing families, noisy workplaces, excessive workloads, a high risk of workplace violence, and emotionally traumatic events [19,[37][38][39]. Additionally, most of the MCH nurses in this study were female (98.2%).…”
Section: Discussionmentioning
confidence: 99%
“…These data support our research data. A study conducted on 181 midwives found that long working hours and exposure to traumatic birth events negatively affected midwives' levels of compassion 43 . Unlike our research, it is also seen that there is a relationship between compassion and working conditions and working hours.…”
Section: Discussionmentioning
confidence: 99%